ANALYSIS OF THE EFFECT OF PRICE AND SERVICE QUALITY ON PURCHASE DECISIONS AT KEDAI COFFEE REMBUKAN JOMBANG - Septi Ambar Indraningtia Sukma; Muhamad Arif; Yessita Puspaningrum (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
As coffee consumption increases, competition among coffee shops in Jombang is becoming increasingly fierce. This requires every business to provide appropriate prices and quality service to influence consumer purchasing decisions. This study aims to determine the effect of price and service quality on purchasing decisions at Kedai Kopi Rembukan Jombang. This study used an associative quantitative approach, distributing questionnaires to 100 respondents selected through purposive sampling. Data analysis was conducted using Instrument Testing, Classical Assumption Testing, Multiple Linear Regression Analysis, and Hypothesis Testing. The results showed that price had a positive and significant effect on purchasing decisions, with a calculated t-value of 3.625 > 1.985 t-table and a significance value of 0.000 < 0.05. Service quality also had a positive and significant effect on purchasing decisions, with a calculated t-value of 5.380 > 1.985 t-table and a significance value of 0.000 < 0.05. The coefficient of determination (R²) value is 0.406, which means that price and service quality are able to explain 40.6% of the variation in consumer purchasing decisions at the Rembukan coffee shop, while the remaining 59.4% is influenced by other factors outside this study. Keywords: Price, Service Quality, Purchasing Decisions, Coffee Shops